WOMEN IN KAZAKHSTAN’S ENERGY INDUSTRIES: IMPLICATIONS FOR ENERGY TRANSITION - Atakhanova, Zauresh; Howie, Peter (Energies, 2022)
Kazakhstan has a relatively high level of overall gender development, as well as of female employment in its energy industries. Diverse views and backgrounds are necessary to address the challenges of curbing emissions in Kazakhstan, a major fossil fuel producer and exporter. However, our analysis of the Labor Force Survey indicates that female representation among energy sector managers and overall workforce has been falling over time. Moreover, we find that women in Kazakhstan’s coal mining, petroleum extraction, and power industries are concentrated in low-skilled and non-core occupations. Next, by analyzing data on labor compensation within energy occupations, we discover signs of persistent vertical discrimination, which may reduce incentives for women to upgrade their skills. Finally, we find that major shocks, such as the COVID-19 pandemic, may stall or reverse prior progress in increasing the energy sector’s gender diversity. Our findings contribute to raising gender awareness among the stakeholders in Kazakhstan’s energy sector in order to facilitate evidence-based gender mainstreaming.
Keywords: Type of access: Open Access; gender; diversity; discrimination; carbon neutrality; net-zero emissions; COVID-19